Limitations of In Vitro Assessments of the Drug Interaction Potential of Botanical Supplements - Markowitz, John S.; Zhu, Hao-Jie (Planta Medica, 2012)
Although there are inherent and recognized limitations of in vitro screening methodologies to assess conventional drug-drug interactions (DDIs) per industry guidelines and those adopted by independent laboratories, further limitations are being appreciated which are unique to the evaluation of botanical products and potential DDIs in which they may participate. Among the larger issues faced are the uncertainty in assigning hepatic concentrations of multiple constituents and their potential metabolites, accounting for oral bioavailability, distribution, first-pass metabolism and active metabolites. Furthermore, the wide variability in the chemical composition of commercially available botanical supplement formulations continues to be a major concern, and manufacturing standards or enforcement thereof is essentially nonexistent in most countries. Differing formulations, unspecified product excipients, administration and absorption of the therapeutic ingredient(s) of a standardized dosage form, the very presence and/or concentration of one or more phytoconstituents within a supplement are typically unknown and nontarget entities. A further issue is the absence of authentic analytical standards, and the inability to accurately screen the entities as mixtures to even approximate typical scenarios, which may occur following the ingestion of dietary supplements, adds additional layers of complexity to experimental design and difficulty in interpreting experimental results. Multiple challenges exist in experimental methodologies employed in performing in vitro research with conventional pharmaceuticals and those unique to botanical extracts. These obstacles prevent the investigators from effectively utilizing high-throughput models to accomplish more than essentially “flag” suspected sources of drug interactions which must be further evaluated in vivo, at present, in order to confirm clinical significance. This review is intended to discuss the problems and challenges in evaluating botanical-drug interactions using in vitro methodologies.
Keywords: botanical; interaction; in vitro; in vivo; metabolism